Method for recycling lead from lead plaster of waste lead-acid storage battery through electrolysis

Through one -step immersion and electrolytic combination process, the corrosion and safety problems in the recycling of waste cream in existing technologies have been solved, and metal lead recycling with high purity and low energy consumption is achieved, which meets the efficient and environmentally friendly process needs.

CN119332305APending Publication Date: 2025-01-21YANGTZE BASIN ECOLOGY & ENVIRONMENT MONITORING & SCIENTIFIC RESEARCH CENTER YANGTZE BASIN ECOLOGY & ENVIRONMENT ADMINISTRATION MINISTRY OF ECOLOGY & ENVIRONMENT OF THE PEOPLES REPUBLIC OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411500269.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing low-energy electrolysis process has corrosive and safety problems in the recycling of waste lead paste, and the process steps are complicated, resulting in problems such as lead dust volatility and sulfur dioxide.

Method used

A neutral lead-containing electrolyte is obtained through one-step leaching, using acetate solution and hydrogen peroxide for leaching. Combined with the electrolysis step, an electrolytic cell design separated by an anion exchange membrane is used to reduce the electrodeposition of copper ions and improve the purity of the lead product.

Benefits of technology

Metal lead recycling with high purity and low impurities content, electrolyte energy consumption is not higher than 600kWh/T lead, the current efficiency is higher than 97%, the lead recovery rate reaches more than 99%, and the corrosion of strong acid and strong alkali is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332305A_ABST
    Figure CN119332305A_ABST
Patent Text Reader

Abstract

The invention discloses a method for recycling lead from waste lead-acid storage battery lead plaster through electrolysis, and belongs to the technical field of solid waste treatment and recycling. The method for recycling lead through electrolysis of the waste lead-acid storage battery lead plaster comprises the following steps that the waste lead-acid storage battery lead plaster, an additional lead source containing metal lead and an acetate solution are mixed and leached, a lead acetate leaching solution is obtained, then the lead acetate leaching solution serves as an electrolyte for electrolysis, and a metal lead product is obtained. According to the method, the lead-containing electrolyte can be obtained through one-step leaching, and the electrolyte is neutral, so that the corrosion of strong acid and strong alkali is avoided. According to the technical method provided by the invention, the metal lead with high purity and low impurity content can be obtained. In the electrolysis step, the electrolysis energy consumption is not higher than 600 kwh / t lead, the current efficiency is higher than 97%, and the lead recovery rate reaches 99% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste treatment and resource utilization, and in particular to a method for recovering lead by electrolyzing lead paste of waste lead-acid batteries. Background Art

[0002] Lead-acid batteries are widely used in automobile starting, backup power, traction power, energy storage and other fields due to their high safety, low price and high recycling rate. The service life of lead-acid batteries is generally 2 to 3 years, and they are recycled and processed centrally after failure. After disassembly, waste lead-acid batteries are divided into four parts: waste lead paste (30 to 40wt%), waste alloy grid (24 to 30wt%), plastic shell (22 to 30wt%) and waste sulfuric acid (11 to 30wt%). The main lead-containing components are waste lead paste and waste alloy grid. The waste alloy grid has a high metallic lead component, and lead ingots are generally obtained by direct low-temperature smelting. Waste lead paste mainly comes from the positive and negative active materials of the battery. Its components are lead sulfate (~50wt%), lead dioxide (~28wt%), lead oxide (~9wt%), metallic lead (~4wt%) and trace impurity elements (Fe, Ba, Sb, etc.). It contains lead compounds with multiple valence states and has a complex composition. It is the most difficult part to recycle in waste lead-acid batteries. At present, waste lead paste is mainly obtained by pyrometallurgical smelting to obtain crude lead, and crude lead is further refined to obtain refined lead products. There are problems such as lead dust volatilization. At the same time, the decomposition of lead sulfate will also produce sulfur dioxide. In view of the shortcomings of the pyrometallurgical process, researchers at home and abroad have begun to study cleaner recycling processes.

[0003] The wet leaching-electrolysis combined preparation of metallic lead process refers to the use of acid or alkali to convert waste lead paste into a lead-containing solution, and then obtain metallic lead through electrodeposition; common leaching agents include HCl-NaCl, H2SiF6, HBF4, etc. However, the traditional electrolysis process in the relevant field has high energy consumption (800-1300kw / t Pb), and the leaching agent is highly corrosive and accompanied by the generation of harmful gases (HF and SiF4, etc.).

[0004] At present, researchers have further improved the low-energy electrolysis process by using different leaching agents (HClO4 or NaOH). The waste lead paste is first desulfurized to convert the PbSO4 in it into PbCO3, and then the desulfurized lead paste is leached with HClO4 to obtain a soluble Pb(ClO4)2 solution. Finally, during the electroplating process, metallic lead is obtained at the cathode, and oxygen is produced by electrolyzing water at the anode. The electrolysis energy consumption of this process is 500kWh / t Pb, the lead recovery rate can reach 98.5%, and the purity of metallic lead can reach 99.9991%. In addition, the waste lead paste can also be catalytically converted and leached with NaOH to obtain a lead-containing alkaline electrolyte, and then metallic lead is obtained at the cathode by electroplating; the lead recovery rate of this method can reach 99.8%, and the electrolysis energy consumption can be reduced to 317kWh / t Pb. It can be seen that the purpose of reducing energy consumption can be achieved by changing the electrolyte system.

[0005] However, the current low-energy electrolysis process still has two problems: (1) the HClO4 and NaOH leaching agents used have corrosive and safety issues; (2) the solid-liquid separation steps are cumbersome; and when HClO4 is used as a leaching agent, desulfurization must be carried out before leaching to obtain desulfurized lead paste. Therefore, it is a technical problem that needs to be solved in this field to construct an electrolytic lead recovery process with green and environmentally friendly leaching agents, fewer process steps, and low energy consumption. Summary of the invention

[0006] The object of the present invention is to provide a method for electrolyzing lead from lead paste of waste lead-acid batteries to solve the above-mentioned problems in the background technology. The present invention can obtain a lead-containing electrolyte by one-step leaching, and the electrolyte is neutral, avoiding the corrosiveness of strong acids and alkalis. The technical method provided by the present invention can obtain metallic lead with high purity and low impurity content. In the electrolysis step of the present invention, the electrolysis energy consumption is not higher than 600kwh / t lead, the current efficiency is higher than 97%, and the lead recovery rate reaches more than 99%.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] One of the technical solutions of the present invention is to provide a method for electrolyzing lead paste of waste lead-acid batteries to recover lead, comprising the following steps:

[0009] The lead paste of waste lead-acid batteries, an additional lead source containing metallic lead and an acetate solution are mixed and leached to obtain a lead acetate leaching solution, and the lead acetate leaching solution is used as an electrolyte for electrolysis to obtain a metallic lead product.

[0010] Preferably, the content of metallic lead in the additional lead source containing metallic lead is 0.3-1 wt % of the mass of the lead paste of the waste lead-acid battery.

[0011] The invention adds an additional lead source containing metallic lead element to reduce the copper ions in the leaching solution and convert the copper ions into lead ions. After the copper ions are reduced to elemental copper, they are separated from the leaching residue by filtration. The invention chooses to remove the copper ions in this way mainly to reduce the electrodeposition of copper ions in the subsequent electrolysis process, thereby improving the purity of the electrodeposited lead product.

[0012] Preferably, the acetate solution is a solution containing acetate and hydrogen peroxide, and the pH value is 6.5-7.5; the acetate is one or more of ammonium acetate, sodium acetate and potassium acetate, and the concentration of the acetate is 5-8 mol / L; the ratio of the added amount of hydrogen peroxide to the lead paste of waste lead-acid batteries is 1.0-3.0 mmol / g.

[0013] Acetate mainly provides acetate ions for complexing lead ions during the leaching process. Hydrogen peroxide mainly reduces lead dioxide in the waste lead paste into divalent lead ions during the leaching process.

[0014] Preferably, the mass volume ratio of the total mass of the lead paste of the waste lead-acid battery and the additional lead source containing metallic lead to the acetate solution is 50-100 g / L.

[0015] Preferably, the leaching temperature is 20-40° C. and the leaching time is 1-6 hours.

[0016] The leaching method of the present invention has a good impurity removal effect. The main impurity metal elements contained in the waste lead paste include iron, barium, copper, antimony, aluminum, calcium, zinc, etc., which show different characteristics during the leaching process. Since the preferred pH value of the leaching solution of the present invention is neutral, the leaching efficiency of iron and aluminum in the reaction system is very low. The barium element mainly exists in the form of stable barium sulfate in the waste lead paste, and the leaching efficiency is relatively low. Copper has a certain leaching rate under this leaching system, but it can be reduced to copper element by adding an external lead source. In addition, antimony, calcium, and zinc also have a certain leaching rate under this leaching system, and need to be removed in combination with the electrolysis step of the present invention.

[0017] Under the preferred leaching conditions of the present invention, efficient leaching of lead can be ensured.

[0018] Preferably, the electrolysis is carried out in an electrolytic cell, which is divided into a cathode chamber and an anode chamber by an anion exchange membrane, lead acetate leaching solution is added to the cathode chamber, and acetate electrolyte is added to the anode chamber.

[0019] More preferably, the type of acetate in the acetate electrolyte is one or more of ammonium acetate, sodium acetate and potassium acetate; the concentration difference between the acetate concentration in the lead acetate leachate and the acetate concentration in the acetate electrolyte is ≤0.05 mol / L; and the volume ratio of the lead acetate leachate to the acetate electrolyte addition amount is 1:1.

[0020] More preferably, the electrolysis temperature is 20-50°C, the time is 5-10 hours, and the current density is 100-300A / m 2 ; The resistance of the anion exchange membrane is less than 5Ω·cm 2 , the maximum allowable current is 500A / m 2 , selectivity ≥90%; the cathode material of the electrolytic cell is a lead plate or lead sheet, and the anode material is a graphite plate or graphite rod.

[0021] During the electrolysis process, lead ions do not pass through the anion exchange membrane, thus avoiding the formation of lead dioxide byproduct in the anode chamber.

[0022] Preferably, the electrolyte further contains an electrolyte additive; the type of the electrolyte additive is sodium lignin sulfonate and / or butyl acetate, and the mass volume ratio of the electrolyte additive to the lead acetate leaching solution is 0.5 to 3 g / L.

[0023] The present invention adjusts the microscopic morphology of the electrodeposited lead product by adding an electrolyte additive into the electrolysis system, thereby obtaining a dense and smooth metallic lead product, so that the lead product is not easy to fall off from the electrode plate during the electrolysis process.

[0024] During the electrolysis process, the reduction potential of lead ions is inconsistent with the reduction potential of other metal ions in the waste lead paste, such as iron, barium, antimony, aluminum, calcium, zinc, and copper. The theoretical order of reduction of various metal ions is Cu 2+ , Pb 2+ , Fe 2+ 、SbO3 - 、Zn 2+ 、Al 3+ , Ca 2+ , Ba 2+ . During the electrolysis process, copper and lead ions are preferentially deposited at the cathode, and iron, antimony, zinc, aluminum, calcium, and barium ions are more difficult to deposit than lead ions, so it has a certain impurity separation effect. For copper ions, since they are reduced to copper element by adding an external lead source containing metallic lead during the leaching process, their content in the electrolyte is very low. Through the combined regulation of leaching and electrolysis, high-purity metallic lead with low impurity element content can be obtained by electrodeposition.

[0025] In the present invention, the separation effects of different impurity elements during leaching and electrolysis are different. For example, for iron, the separation of iron elements plays a dominant role during leaching, and although iron elements are more difficult to deposit than lead elements during electrolysis, there will still be iron electrodeposition under the current defined by the present invention and the voltage window formed by the electrolysis system. If the iron element separation effect of the step before electrolysis does not meet the requirements, it is difficult to meet the requirements for the iron content in the electrodeposited lead product; for barium, both leaching and electrolysis processes have good impurity separation effects. Therefore, in order to achieve efficient separation of multiple impurity elements and control the impurity element content in the electrodeposited product at a low level, it is necessary to jointly regulate leaching and electrolysis.

[0026] According to the national standard "Lead Ingot" (GB / T469-2023), the recovery method of the present invention is applicable to the electrolytic refining production of lead ingots of two grades, Pb99.996 and Pb99.994. The content of impurity elements in the obtained metallic lead product meets the following conditions: copper ≤ 8 mg / kg, antimony ≤ 8 mg / kg, zinc ≤ 4 mg / kg, and iron ≤ 5 mg / kg.

[0027] Preferably, after the electrolysis is completed, the electrolyte remaining from the electrolysis is collected from the cathode chamber, then mixed with barium acetate, reacted for 0.5 to 6 hours, and then crystallized and purified for 12 to 24 hours in an environment of 40 to 80° C., and solid-liquid separation is performed to obtain barium sulfate by-product.

[0028] Since the electrolyte contains sulfate ions remaining in the leaching process, in order to achieve the recycling of the electrolyte and ensure the subsequent efficient leaching of waste lead paste, it is necessary to remove the sulfate ions in the solution.

[0029] Preferably, the solution obtained by solid-liquid separation is used to prepare the acetate solution for the next cycle; ammonium acetate is added to the solution obtained by solid-liquid separation in an amount of 2.5 to 7.5 wt % of the amount of ammonium acetate used in the first round, and the content of hydrogen peroxide is added to a ratio of 1.0 to 3.0 mmol / g to the lead paste of waste lead-acid batteries, and acetic acid is used to adjust the pH of the solution to 6.5 to 7.5. In addition, no exogenous lead powder is added, but the metal lead product of the previous round of electrolysis is used, and the amount of the metal lead product added is 0.3 to 1 wt % of the mass of the waste lead paste.

[0030] Preferably, the obtained metallic lead product is used as an additional lead source in the next round of cyclic reaction; the metallic lead content in the metallic lead product is 0.3-1wt% of the mass of the lead paste of the waste lead-acid battery.

[0031] The electrolyte remaining after electrolysis of the present invention can be used to remove sulfate ions in the electrolyte by adding barium salt to obtain barium sulfate byproduct, and the separated solution can be used for the next cycle to achieve recycling, effectively reducing the reagent consumption in the electrolysis process and improving the economy of the electrolysis process.

[0032] The beneficial technical effects of the present invention are as follows:

[0033] The present invention can obtain a lead-containing electrolyte through one-step leaching, and the electrolyte is neutral, thus avoiding the corrosiveness of strong acids and alkalis.

[0034] The technical method provided by the invention can obtain metallic lead with high purity and low impurity content.

[0035] In the electrolysis step of the present invention, the electrolysis energy consumption is no more than 600 kwh / t lead, the current efficiency is higher than 97%, and the lead recovery rate reaches more than 99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 Schematic diagram of the preparation steps of Example 1 of the present invention.

[0038] Figure 2 This is a SEM image of the metallic lead product obtained in step (2) of Example 1 of the present invention.

[0039] Figure 3 This is the XRD spectrum of the metallic lead product obtained in steps (2) to (4) in Example 1 of the present invention.

[0040] Figure 4 This is the XRD spectrum of the barium sulfate by-product obtained in steps (2) to (4) in Example 1 of the present invention.

[0041] Figure 5 The following are SEM images and surface images of the metal lead products obtained in step (2) of Example 4 and Comparative Example 1. (a) is the SEM image of Comparative Example 1, (b) is the SEM image of Example 4, (c) is the surface image of Comparative Example 1, and (d) is the surface image of Example 4. DETAILED DESCRIPTION

[0042] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0043] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0044] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0045] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0046] The "room temperature" in the present invention is 20-30°C unless otherwise specified.

[0047] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0048] Example 1

[0049] A method for recovering lead from lead paste of waste lead-acid batteries by electrolysis, comprising the following steps:

[0050] (1) 1 wt % of metallic lead is added to the lead paste of waste lead-acid batteries to obtain a solid phase component, which is then mixed with an ammonium acetate solution at a solid-liquid ratio of 90 g / L, leached at room temperature for 2 h, and filtered to separate the solid and liquid to obtain a lead acetate leaching solution with a lead ion concentration of 0.30 mol / L (the lead leaching rate of this step is measured to be 97.26%); the ammonium acetate solution is a solution containing ammonium acetate and hydrogen peroxide, with a pH of 7.2, a concentration of ammonium acetate of 7 mol / L, and a ratio of the amount of hydrogen peroxide added to the lead paste of waste lead-acid batteries of 2.2 mmol / g.

[0051] (2) 1 g / L sodium lignin sulfonate is added to the lead acetate leaching solution, and then added to the cathode chamber of the electrolytic cell, and then 0.30 mol / L ammonium acetate electrolyte is added to the anode chamber of the electrolytic cell, and the volume ratio of the lead acetate leaching solution to the ammonium acetate electrolyte is 1:1. The cathode chamber and the anode chamber of the electrolytic cell are separated by an anion exchange membrane, and the anode and cathode are respectively selected from lead plates and graphite plates; the resistance of the anion exchange membrane is 4.0 Ω·cm 2 , the maximum allowable current is 500A / m 2 , the selectivity is 95%. The current density is controlled to be 300A / m 2 , the electrolysis temperature is 40°C, the electrolysis is carried out for 6.5 hours, and then the metallic lead product (purity is 99.996%) is obtained at the cathode plate. It has been determined that the electrolysis energy consumption during the electrolysis process is 600 kWh / t lead, the current efficiency is 97.2%, and the lead recovery rate is 99.4%.

[0052] After the electrolysis is completed, the remaining electrolyte is collected from the cathode chamber, and then 46 g / L of barium acetate is added to react for 2 hours, and then crystallized and purified for 12 hours in a 40°C environment, and solid-liquid separation is performed to obtain barium sulfate by-product.

[0053] (3) The filtrate obtained after solid-liquid separation is used to prepare the leaching solution for the next cycle; ammonium acetate is added to the filtrate, and the amount of ammonium acetate added is 2.5wt% of the amount of ammonium acetate used in the first round, and the content of hydrogen peroxide is added to a ratio of 2.2mmol / g to the lead paste of the waste lead-acid battery, and acetic acid is used to adjust the solution pH to 7.2 to prepare the second round of leaching solution.

[0054] The metallic lead product obtained in step (2) is added to the lead paste of the waste lead-acid battery (the metallic lead content of the metallic lead product is 1 wt% of the mass of the lead paste of the waste lead-acid battery) to obtain a solid phase component, which is then mixed with an ammonium acetate solution at a solid-liquid ratio of 90 g / L, leached at room temperature for 2 h, and filtered to separate the solid and liquid to obtain a lead acetate leaching solution with a lead ion concentration of 0.30 mol / L (the lead leaching rate of this step is measured to be 97.20%).

[0055] Then, electrolysis is carried out according to the conditions of step (2) to obtain metallic lead product and barium sulfate by-product after two cycles.

[0056] (4) Repeat step (3) three times to obtain metallic lead product and barium sulfate by-product after three, four, and five cycles.

[0057] It was determined that the lead leaching rates of the lead acetate leaching solutions obtained after three, four and five cycles were 96.89%, 97.01% and 96.64% respectively. The impurity element contents in the metallic lead products obtained after five cycles all met the following conditions: the iron content was less than 5 mg / kg, the barium content was less than 3 mg / kg, the copper content was less than 7 mg / kg, the antimony content was less than 7 mg / kg, the zinc content was less than 4 mg / kg, the aluminum content was less than 3 mg / kg, and the calcium content was less than 5 mg / kg.

[0058] Figure 1 Schematic diagram of the preparation steps of Example 1 of the present invention.

[0059] Figure 2 This is a SEM image of the metallic lead product obtained in step (2) of Example 1 of the present invention.

[0060] Figure 3 This is the XRD spectrum of the metallic lead product obtained in steps (2) to (4) in Example 1 of the present invention.

[0061] Figure 3 In the figure, Cycle1, Cycle2, Cycle3, Cycle4, and Cycle5 refer to the metallic lead products after one, two, three, four, and five cycles, respectively.

[0062] Figure 4 This is the XRD spectrum of the barium sulfate by-product obtained in steps (2) to (4) in Example 1 of the present invention.

[0063] Figure 4 In the figure, Cycle1, Cycle2, Cycle3, Cycle4, and Cycle5 refer to the barium sulfate byproduct after one, two, three, four, and five cycles, respectively.

[0064] It can be seen from the relevant data that in the subsequent multiple cycles, the leaching efficiency of the leaching step did not decrease significantly, the metallic lead product obtained by electrolysis still maintained a high purity, and the content of impurity elements was effectively controlled.

[0065] Example 2

[0066] The only difference from Example 1 is that the concentration of ammonium acetate in step (1) is modified to 6 mol / L.

[0067] According to statistics, a lead acetate leaching solution with a lead ion concentration of 0.29 mol / L (lead leaching rate of 96.21%) was obtained in 5 cycles. The electrolysis energy consumption in the electrolysis process of 5 cycles was 590 kwh / t lead, the current efficiency was 98.2%, and the lead recovery rate was 99.0%. The impurity element contents in the metallic lead product obtained after 5 cycles all met the following conditions: the iron content was less than 5 mg / kg, the barium content was less than 3 mg / kg, the copper content was less than 7 mg / kg, the antimony content was less than 7 mg / kg, the zinc content was less than 4 mg / kg, the aluminum content was less than 3 mg / kg, and the calcium content was less than 5 mg / kg.

[0068] Example 3

[0069] The only difference from Example 1 is that the current density in step (2) is changed to 200 A / m 2 .

[0070] According to statistics, lead acetate leaching solution with a lead ion concentration of 0.30 mol / L (lead leaching rate of 97.26%) was obtained in 5 cycles. The electrolysis energy consumption in the electrolysis process of 5 cycles was 580 kwh / t lead, the current efficiency was 98.5%, and the lead recovery rate was 99.1%. The impurity element contents in the metallic lead product obtained after 5 cycles all met the following conditions: the iron element content was less than 5 mg / kg, the barium element content was less than 3 mg / kg, the copper element content was less than 7 mg / kg, the antimony element content was less than 7 mg / kg, the zinc element content was less than 4 mg / kg, the aluminum element content was less than 3 mg / kg, and the calcium element content was less than 5 mg / kg.

[0071] Example 4

[0072] The only difference from Example 1 is that in step (2), 1 g / L of sodium lignin sulfonate is added to the lead acetate leaching solution and 1 g / L of butyl acetate is added.

[0073] Comparative Example 1

[0074] The only difference from Example 1 is that the addition of electrolyte additives (sodium lignin sulfonate and butyl acetate) into the electrolyte is omitted.

[0075] Figure 5 The following are SEM images and surface images of the metal lead products obtained in step (2) of Example 4 and Comparative Example 1. (a) is the SEM image of Comparative Example 1, (b) is the SEM image of Example 4, (c) is the surface image of Comparative Example 1, and (d) is the surface image of Example 4.

[0076] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for recovering lead from lead paste of waste lead-acid batteries by electrolysis, characterized in that: The following steps are involved: The lead paste of waste lead-acid batteries, an additional lead source containing metallic lead and an acetate solution are mixed and leached to obtain a lead acetate leaching solution, and the lead acetate leaching solution is used as an electrolyte for electrolysis to obtain a metallic lead product.

2. The method according to claim 1, characterized in that The content of metallic lead in the additional lead source containing metallic lead is 0.3-1wt% of the mass of the lead paste of the waste lead-acid battery.

3. The method according to claim 1, characterized in that The acetate solution is a solution containing acetate and hydrogen peroxide, and the pH value is 6.5-7.5; the acetate is one or more of ammonium acetate, sodium acetate and potassium acetate, and the concentration of the acetate is 5-8 mol / L; the ratio of the hydrogen peroxide to the lead paste of the waste lead-acid battery is 1.0-3.0 mmol / g.

4. The method according to claim 1, characterized in that The mass volume ratio of the total mass of the lead paste of the waste lead-acid battery and the additional lead source containing metallic lead to the acetate solution is 50-100 g / L.

5. The method according to claim 1, characterized in that The leaching temperature is 20-40° C. and the leaching time is 1-6 hours.

6. The method according to claim 1, characterized in that The electrolysis is carried out in an electrolytic cell, which is divided into a cathode chamber and an anode chamber by an anion exchange membrane. Lead acetate leaching solution is added to the cathode chamber, and acetate electrolyte is added to the anode chamber.

7. The method according to claim 6, characterized in that The electrolysis temperature is 20-50°C, the time is 5-10 hours, and the current density is 100-300A / m 2 ; The resistance of the anion exchange membrane is less than 5Ω·cm 2 , the maximum allowable current is 500A / m 2 , selectivity ≥90%; the cathode material of the electrolytic cell is a lead plate or lead sheet, and the anode material is a graphite plate or graphite rod.

8. The method according to claim 1, characterized in that The electrolyte also contains electrolyte additives; the electrolyte additives are sodium lignin sulfonate and / or butyl acetate, and the mass volume ratio of the electrolyte additives to the lead acetate leaching solution is 0.5 to 3 g / L.